A cephalometric evaluation of adult Filipino female population (aged 18 to 35 years old) using the computerized Moorrees Mesh Coordinate System - Naseri, Sara Haghighat
The aim of this study was to established reference norms for Filipino female adults using the Moorrees Mesh Coordinate System. The lateral cephalograms of 30 Class I female subjects, with a mean age of 21.10 years, were traced. Nine (9) soft tissue landmarks and twenty five (25) hard tissue landmarks were identified. The mean proportionate locations of the anatomic landmarks, within their respective mesh rectangles were calculated. The cephalometric measurements were recorded and compared with Moorrees' Caucasian female norms, the Puerto-Rican female and African-American female ethnic groups. The Filipino normative diagram was created and subsequently comapre with Moorrees' Caucasian female diagram, Evanko's Puerto-Rican female diagram and Faustini's African-American female diagram. Strata V.6 sample t-test was used for the statistical analysis. Results confirmed racial or ethnic differences exist in the craniofacial complex. Comparisons revealed that craniofacial similarities between the Filipino and the Caucasian females were generally limited to the lower border of the mandible. The Filipino and the Puerto-Rican females demonstrated a similar soft tissue profile in terms of form but not in the anteroposterior position. In the same manner, the similarity between the Filipino and the African-American females was specifically confined to the bimaxillary protrusion of the incisors only in terms of inclination, but not in the anteroposterior position. In conclusion, statistical evaluation showed significant differences exist between the Filipino females vis-a-vis the three ethnic groups in the majority of the landmarks located in the skeletal, dental and alveolar areas, both in the vertical and horizontal directions.